Hernia Surgery and Recent Developments - Malik, Arshad M. (IntechOpen, 2018)
This book highlights the hernia as an ancient disease that has affected the mankind all over the world with a very high frequency. The book contains a brief introductory chapter followed by various chapters emphasizing the evolution of hernia surgery from the very basic operations to the present highly advanced technique use in present era to treat this surgical problem. Hopefully, this book will be of significant benefit to the trainee and practicing surgeons alike.